Analisis Semantik Leksikal dan Kontekstual pada Lirik Lagu "Mangu" oleh Fourtwnty Ft. Charita Utami (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to analyze the lexical and contextual meanings in the lyrics of the song “Mangu” by Fourtwnty Ft. Charita Utami. This song was chosen because it contains emotional, symbolic, and reflective messages that reflect inner turmoil and value conflicts in human relationships. The method used is a descriptive qualitative approach with semantic analysis techniques. Data was obtained from the song lyrics and analyzed through the stages of identifying lexical meaning based on the literal meaning of the words, and contextual meaning based on the situation and context of their use. The results of the study indicate that the lyrics of “Mangu” contain various forms of lexical meaning such as synonyms, antonyms, collocations, polysemy, and idioms, as well as contextual meaning reflecting spiritual conflict, differences in principles, and the search for identity. This song symbolically represents the social conditions often experienced by individuals in personal and existential relationships. These findings enrich the study of semantics in popular literary works and can be implemented in Indonesian language learning as contextual and meaningful teaching materials.